2021
DOI: 10.3389/fphar.2021.604928
|View full text |Cite
|
Sign up to set email alerts
|

The Non-Steroidal Mineralocorticoid Receptor Antagonist KBP-5074 Limits Albuminuria and has Improved Therapeutic Index Compared With Eplerenone in a Rat Model With Mineralocorticoid-Induced Renal Injury

Abstract: The therapeutic indices (TIs) and efficacy of the non-steroidal mineralocorticoid receptor antagonist (MRA) KBP-5074 and steroidal MRA eplerenone were evaluated in a uninephrectomized Sprague Dawley rat model of aldosterone-mediated renal disease. In two parallel studies, rats were placed on a high-salt diet and received aldosterone by osmotic mini-pump infusion over the course of 27 days. The urinary albumin-to-creatinine ratio (UACR) was evaluated after 7, 14, and 26 days of treatment. Serum K+ was evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 26 publications
(33 reference statements)
0
9
0
Order By: Relevance
“…The non-steroidal MRAs SM-368229 (N-4,4-dimethyl-2-thioxo-1,4-dihydro-2H-3,1-benzoxazin-6-ylthiophene-2-sulfonamide), CS-3150 (esaxerenone) and AZD9977 have also shown promising effects on renal pathology in this context (Arai et al, 2016;Bamberg et al, 2018;Nariai et al, 2012). Similarly, the non-steroidal MRA KBP-5074 showed a better therapeutic index than eplerenone in a rat model of kidney injury induced by aldosterone, salt and unilateral nephrectomy (Jaisser et al, 2021). Of note, AZ9977 showed a reduced effect on renal sodium excretion relative to that of eplerenone, while retaining its renal protection benefit (Bamberg et al, 2018).…”
Section: Mr Antagonism Alleviates Kidney Injury In Various Preclinica...mentioning
confidence: 99%
“…The non-steroidal MRAs SM-368229 (N-4,4-dimethyl-2-thioxo-1,4-dihydro-2H-3,1-benzoxazin-6-ylthiophene-2-sulfonamide), CS-3150 (esaxerenone) and AZD9977 have also shown promising effects on renal pathology in this context (Arai et al, 2016;Bamberg et al, 2018;Nariai et al, 2012). Similarly, the non-steroidal MRA KBP-5074 showed a better therapeutic index than eplerenone in a rat model of kidney injury induced by aldosterone, salt and unilateral nephrectomy (Jaisser et al, 2021). Of note, AZ9977 showed a reduced effect on renal sodium excretion relative to that of eplerenone, while retaining its renal protection benefit (Bamberg et al, 2018).…”
Section: Mr Antagonism Alleviates Kidney Injury In Various Preclinica...mentioning
confidence: 99%
“…These beneficial actions were confirmed in stroke‐prone spontaneously hypertensive rats, in which KBP‐5074 also inhibited the increase in BP, reduced urinary albumin excretion and decreased kidney‐to‐body and heart‐to‐body weight ratios (Chow et al, 2017). Recently, a comparative study with eplerenone in high‐salt diet‐fed rats with aldosterone infusion showed an improved efficacy and therapeutic index, calculated as the ratio of the EC 50 for increasing K + to the EC 50 of decreasing UACR, with KBP‐5074 (Jaisser et al, 2021). Preclinical analyses were completed by toxicity and safety studies in rats and dogs, in which no toxicity and good tolerability were demonstrated (Chow et al, 2018).…”
Section: Novel Non‐steroidal Mrasmentioning
confidence: 99%
“…In response to concerns about the benefit-safety profile of steroidal MRAs, several new selective nonsteroidal MRAs were developed with the dual goal of improving efficacy and reducing unwanted side effects, primarily hyperkalemia. 3,32 Figure 2 provides a direct comparison between the steroidal MRAs (spironolactone and eplerenone) and the recently approved and most widely investigated Representative examples compiled from Jaisser et al, 2 Kintscher et al, 3 Buonafine et al, 8 Fuller et al, 9 and Barrera-Chimal et al 15 Abbreviations: CKD, chronic kidney disease; eNOS, endothelial nitric oxide synthase; ICAM-1, intercellular adhesion molecule 1; MCP-1, monocyte chemoattractant protein 1; MR, mineralocorticoid receptor; MRA, mineralocorticoid receptor antagonist; NADPH, reduced nicotinamide adenine dinucleotide phosphate; Nox2, NADPH oxidase 2; Rac1, Rac family small guanosine triphosphatase 1; VCAM-1, vascular cell adhesion molecule 1.…”
Section: Novel Nonsteroidal Mrasmentioning
confidence: 99%
“…Strong evidence has now accumulated to show that MR activation leads to many "off-target" effects on the heart, the vasculature, and the kidney. [1][2][3] In this review, we summarize our growing understanding of role of MR activation in propagating kidney injury, inflammation, and fibrosis and the consequent progression of CKD. We review the recent clinical studies that investigated and defined the efficacy of MR antagonism in attenuating progressive kidney disease 4,5 and that culminated in an MR antagonist (MRA) becoming an approved treatment for retarding CKD progression.…”
mentioning
confidence: 99%